TEORI BELAJAR HUMANISTIK CARL ROGERS DAN IMPLEMENTASINYA DALAM PENDIDIKAN AGAMA ISLAM - Fadli, Muhammad Ulfi (STAINU Purworejo, 2021)
This article aims to find out how to implement the humanistic learning theory brought by one of the characters, Carl Rogers. The method used in this research uses analytical literature study and data taken from books, journals and other literature relevant to the implementation of Carl Rogers' humanistic learning theory in Islamic religious education learning. The results showed that the humanistic theory of Carl Rogers is relevant to be implemented in Islamic religious education, although not all materials can be applied through this humanistic theory. An effective way is by discussing several stages in which he is guided by an educator who acts as a facilitator. The facilitator has the task of guiding, supervising, and ensuring that the discussion process runs smoothly so that the transfer of knowledge can run optimally through this method. Keyword : Learning Theory, Islamic Religious Education, Humanistic